Impact of COVID-19 post lockdown on eating habits and lifestyle changes among university students in Bangladesh: a web based cross sectional study - Imran, Faysal Ahmed; Khatun, Mst Eshita (International Journal Of Community Medicine And Public Health, 2022)
Background: Since the confinement of the lockdown, universities transferred their teaching and learning activities in online as an all-out intention to prevent the transmission of the infection. This study aimed to determine the significant changes in food habits, physical activity, sleeping hours, shopping habits, Internet use time and mental status of the students and investigate the associations between variables. Methods: The study participants were 307 Undergraduate students, between 18 and 25 years of age completed a structured questionnaire from January 3, 2022 to February 13, 2022. The questionnaire included demographic information of the students, questionnaire of dietary pattern, physical activity, sleep quality index, Shopping practice and Internet use time. Chi-square tests were used to associate the baseline information with lifestyle changes in post lockdown. Results: The study reveals that 21.5% of respondents gained weight, 23.8% lost their weight and 41.7% controlled their weight. Eating of homemade food decreased after lockdown 76.5% and eating of restaurant food increased after lockdown 23.5%. A number of major meals 3-4 meals per day decreased after lockdown 61.9%. Physical exercise significantly increased after lockdown (p=0.001). Sleeping hours per day significantly decreased after lockdown (p=0.001), sleep quality was almost the same and energy level increased more in post lockdown. Respondents felt mentally tired after lockdown 60.9%. Respondents spending time on the Internet in chat rooms was 88.3%. Conclusions: This study represents the significant impact on food habits, mental health, and daily routine of students after lockdown, suggesting that we should maintain a balanced diet, physical exercise to improve sleep quality and mental health.